Enzymatic synthesis, characterization and properties of the protein-polysaccharide conjugate: A review. (15th March 2022) - Wu, Tongfeng; Liu, Chengmei; Hu, Xiuting
Highlights: The protein-polysaccharide conjugate can be prepared by enzymatic crosslinking. Transglutaminase, laccase, or peroxidase is used to synthesize the conjugate. Transglutaminase couples proteins and amine-containing polysaccharides. Laccase and peroxidase conjugate proteins and feruloylated polysaccharides. The protein-polysaccharide conjugate has improved solubility and other properties. Abstract: Poor solubility of proteins negatively affects their functional properties and greatly limits their application. Enzymatic cross-linking with polysaccharides can improve solubility and functional properties of proteins. The enzymes used include transglutaminase, laccase and peroxidase. Therefore, this work introduces the cross-linking mechanisms of these enzymes and the characterization techniques, the improved properties and the potential applications of the enzymatically-synthesized protein-polysaccharide conjugate. Transglutaminase catalyzes the formation of a new peptide bond and thus works on amino-containing polysaccharides to conjugate with proteins. However, laccase and peroxidase catalyze oxidation of various compounds with phenol and aniline structures. Therefore, these two enzymes can catalyze the conjugate reaction between proteins and feruloylated polysaccharides which are widely distributed in cereal bran. Compared with the unmodified protein, the enzymatically-synthesized protein-polysaccharide conjugate usually has higher solubility and better functional properties. Thus, it is inferred that enzymatic conjugation with polysaccharide molecules can extend the application of proteins.